1986
DOI: 10.3109/01480548609042831
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Depletion by Phorone Organ Specificity and Effect on Hepatic Microsomal Mixed-Function Oxidase System

Abstract: Phorone (diisopropylidene acetone) led to a strong depletion of cellular glutathione in liver, kidney and heart but not in lung or brain upon administration to mice or rats. Its efficacy in lowering hepatic glutathione levels was comparable to that of diethylmaleate. Unlike this agent, however, phorone did not affect the microsomal mixed-function oxidase system at all. Our findings favor the use of phorone when studying the effect of a decreased glutathione content on detoxication, bioactivation or drug metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In a recent study we showed that potassium bromate activated the Nrf2 and p53 response without activation of the ATF4 response (Limonciel et al, 2018 ). Phorone can similarly activate Nrf2 due to glutathione depletion (Younes et al, 1986 ; Iannone et al, 1990 ; Oguro et al, 1996 ). Tunicamycin is a prototypical activator of the unfolded protein response (including the ATF4 branch) by causing an accumulation of misfolded glycoproteins in the ER (Oslowski and Urano, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study we showed that potassium bromate activated the Nrf2 and p53 response without activation of the ATF4 response (Limonciel et al, 2018 ). Phorone can similarly activate Nrf2 due to glutathione depletion (Younes et al, 1986 ; Iannone et al, 1990 ; Oguro et al, 1996 ). Tunicamycin is a prototypical activator of the unfolded protein response (including the ATF4 branch) by causing an accumulation of misfolded glycoproteins in the ER (Oslowski and Urano, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P-450 content, NADPH-cytochrome c reductase activity, aminopyrine demethylation capacity, as well as the production of . O 2 -and H 2 O 2 were unaffected by phorone treatment (Younes et al, 1986). Phorone treatment also had no effect on lipid peroxidation, glutathione peroxidase and superoxide dismutase activity, thus this agent seems to be a valuable tool as it merely leads to glutathione depletion (Mehmetcik et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the hepatic content of glutathione as measured by the method od Sedlack & Lindsay (1968) valued 0.39&0.09 pmol/g as compared to 7.45k0.66 pmol/g in control rats (meanskS.E.M., n = 8 each). Phorone has been previously shown not to influence microsomal enzyme activities which are responsible for halothane bioactivation (Younes et al 1986). In the respective experiments, deferrioxamine (500 mg/kg in 10 ml/kg 0,9% NaCl solution intraperitoneally) diethyldithiocarbamate or (+)-catechin (200 mg/kg in 10 ml/kg 1 % carboxymethylcellulose solution orally each) were administered 30 min.…”
Section: Methodsmentioning
confidence: 99%